Assessment of a hybrid propulsion system for short-mid range application with a low-order code - Amerini, Alberto; Langone, Leonardo; Vadi, Riccardo; Andreini, Antonio (E3S web of conferences, 2021)
The increase in air traffic expected in the next years must be accompanied by innovation to ensure the lowest possible environmental impact. Hybrid electric-thermal propulsion systems are currently being investigated and could represent a breakthrough for environmental sustainability in the sector. However, the transition to electric propulsion remains challenging due to the current level of energy density related to storage systems, the additional components associated with power conversion and control systems, not to mention the cost of all the associated equipment. The purpose of this study is to carry out a preliminary assessment of a hybrid propulsion system for a short-mid range aircraft. This study investigates the series hybrid configuration, where a turboshaft, a high temperature superconducting (HTS) electric motor, batteries and power converters interact to provide the necessary propulsion for flight. A zero-dimensional procedure is developed to estimate the mass and efficiency of the powertrain components for a selected flight mission. Thermal engines are modeled with the low-order code and coupled with the components of the electric system through a python routine. A comparison in terms of weight and emissions is reported for the designed hybrid propulsion system and the conventional one. The analysis shows that the weight of the two propulsion systems is similar but, the presence of batteries, even considering a higher level of technology than the current one, leads to a significant increase in the weight of the hybrid aircraft. The second part of the study focuses on pollutant emissions, showing that the hybrid system can reduce CO 2 emissions by 58% and NOx emissions by 68% compared to the conventional system. Despite the excellent premise, the reduction in payload for the hybrid aircraft causes a reduction in pollutant emissions per passenger only for NOx. For this reason, further technological improvement is needed to make hybrid propulsion advantageous in terms of both payload and pollutant emissions.